CASE REPORT: PRESERVATION OF THE ALVEOLAR RIDGE FOR SUCCESSFUL FIXED ZIRCONIA DENTAL RESTORATION - Stojanoski, Magdalena; Paneva, Maja; Stojanoski, Ivan; Naumova, Angela; Mijoska, Aneta (Journal of Morphological Sciences; Vol 8 No 1 (2025): JMS, 2025)
Alveolar ridge preservation is a common dental procedure designed to preserve the space left after tooth extraction. It involves the use of a natural collagen membrane derived from the porcine pericardium, used alone, or in combination with a bone graft to replace missing bone before implant placement and prosthodontic reconstruction. This case report aims to demonstrate the importance of alveolar ridge preservation after tooth extraction, the method, and its outcome for successfully placing a fixed prosthetic construction. Case report: The technique uses a natural collagen membrane (Jason membrane) derived from porcine pericardium that can be resorbed, in combination with the xenogeneic bone graft (Carebone, Botiss) and subsequent zirconium dioxide fabrication after 6 months in a 45-year-old female patient. Conclusion: Regeneration of the alveolus with Jason membrane and artificial bone Carebone, can minimize further bone resorption and allow for successful placement of prosthetic solution. Keywords : extraction, alveolus, alveolar ridge, PMMA, zirconium crowns.